Non-Lorentzian SU(1, n) Spacetime Symmetry In Various Dimensions - Lambert, N.; Mouland, R.; Orchard, T. (Frontiers in Physics, 2022)
We discuss non-Lorentzian Lagrangian field theories in 2n-1 dimensions that admit an SU(1,n) spacetime symmetry which includes a scaling transformation. These can be obtained by a conformal compactification of a 2n-dimensional Minkowskian conformal field theory. We discuss the symmetry algebra, its representations including primary fields and unitarity bounds. We also give various examples of free theories in a variety of dimensions and a discussion of how to reconstruct the parent 2n-dimensional theory.